Pembelajaran Bahasa Indonesia dengan Pendekatan Multiliterasi - Afifah Azzahra; Irwan Siagian (Departement of Mathematics Education, 2024)
Indonesian language learning in the digital era faces the challenges of globalization and rapid technological advancement. The multiliteracy approach emerges as a significant innovation in teaching methods to address these challenges. This approach integrates various types of literacy such as digital literacy, media literacy, visual literacy, and critical literacy to enhance the quality of learning. Through a literature review, this study explores the benefits of the multiliteracy approach in Indonesian language learning. The review results indicate that the use of technology in learning can increase student engagement and enrich their learning experiences. Students who use technology in learning show significant improvements in their literacy skills compared to conventional methods. Furthermore, the role of the teacher as a facilitator is crucial in this approach, where the quality of teaching, the feedback given, and student engagement are key factors influencing learning outcomes. Moreover, digital literacy skills are closely related to communication skills. Students involved in collaborative projects using technology show significant improvements in their writing and speaking abilities. The multiliteracy approach also helps students develop more effective and in-depth communication skills, which are highly needed in the 21st century.